2020
DOI: 10.3390/foods9010064
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Concentrate as a Novel Source of Bifunctional Peptides with Angiotensin-I Converting Enzyme Inhibitory and Antioxidant Properties: RSM Study

Abstract: Whey protein concentrate (WPC) is a unique source of protein with numerous nutritional and functional values due to the high content of branched-chain amino acid. This study was designed to establish the optimum conditions for Alcalase-hydrolysis of WPC to produce protein hydrolysates with dual biofunctionalities of angiotensin-I converting enzyme (ACE) inhibitory and antioxidant activities via response surface methodology (RSM). The results showed that the optimum conditions were achieved at temperature = 58.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…There were no statistically significant differences in ACE-inhibitory activity between the ALC (87.93 ± 3.57%), CHY (92.10 ± 2.64%), and FLA (82.08 ± 6.06%) hydrolysates. As the results obtained in this work, previous studies have obtained whey protein hydrolysates with antioxidant and ACE-inhibitory properties (Corrêa et al, 2014;Hussein et al, 2020;Martín-del-Campo et al, 2019;O'Keeffe et al, 2017). As antioxidant activity, ACEinhibitory capacity depends on enzyme specificity that can affect the composition of each hydrolysates in terms of peptide and their amino acid composition.…”
Section: Optimization Of the Parameters Of Hydrolysis And Validation Of Modelsupporting
confidence: 55%
See 3 more Smart Citations
“…There were no statistically significant differences in ACE-inhibitory activity between the ALC (87.93 ± 3.57%), CHY (92.10 ± 2.64%), and FLA (82.08 ± 6.06%) hydrolysates. As the results obtained in this work, previous studies have obtained whey protein hydrolysates with antioxidant and ACE-inhibitory properties (Corrêa et al, 2014;Hussein et al, 2020;Martín-del-Campo et al, 2019;O'Keeffe et al, 2017). As antioxidant activity, ACEinhibitory capacity depends on enzyme specificity that can affect the composition of each hydrolysates in terms of peptide and their amino acid composition.…”
Section: Optimization Of the Parameters Of Hydrolysis And Validation Of Modelsupporting
confidence: 55%
“…A longer time of hydrolysis and higher E:S ratio could cause the degradation chelating peptides previously TA B L E 6 Experimental and predicted values for response variables using optimal conditions for enzymatic hydrolysis of WPC with alcalase (ALC), chymotrypsin (CHY), and flavourzyme (FLA) produced. Hussein et al (2020) reported a negative relation of the E:S ratio on iron-chelating activity. By contrast, chelating ability increased as hydrolysis progressed until a maximum value and then decreased with longer times of hydrolysis.…”
Section: Antioxidant Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…Hussein et al [ 11 ] investigated the hydrolysis of WPC by alcalase by means of response surface methodology. The aim of the study was to determine the appropriate conditions for the production of protein hydrolysates with dual biofunctionalities, that is, angiotensin-I converting enzyme (ACE) inhibitory and antioxidant activities.…”
mentioning
confidence: 99%